Study of a silica glass SiO2-Na2O refractive index to fabrication of fiber optic with Brewster method - Ahmad Aftah Syukron; Isnaini Lilis Elviyanti (Journal of Physics: Theories and Applications, 2019)
One of the critical parameters in the fabrication of fiber optic is refractive index value from the fiber optic material. That is because the main requirement phase of critical angle on the fiber optic waveguide is a core refractive index higher than the cladding. Therefore, refractive index values must be calculated first. The research aim  is to study refractive index value of  fiber optic material on the fiber optic fabrication. Refractive index value determined by using the brewster method. For this aim, the first step is an establish glass silica to a thin plate. Then thin plate inserts to the sketch of brewster experiment. The brewster method has the aim to determine the reflectance value of the light on transfer magnetic (TM) polarization. The Brewster angle determined by searching the minimum reflectance value of the light on this TM polarization. In this research, the brewster angle obtained by 55.333 degrees. This brewster angle used to calculate the refractive index value from the fiber optic material glass silica. The result of refractive index value at 1.446.